This PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAME EDUKASI WORDWALL TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS KELAS V SDN 1 HAURPANGGUNG - Mentary Sopiawati Pazri; Dea Asri Pujiasti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the educational game media Wordwall on the English vocabulary mastery of fifth-grade students at SDN 1 Haurpanggung. The research design used was a one group pre-test and post-test design. The sample consisted of 29 students of class V-A at SDN 1 Haurpanggung. Data were collected through a vocabulary mastery test administered before (pre-test) and after (post-test) the use of Wordwall. The results showed that the average pre-test score was 58.79, while the average post-test score increased to 81.55. The paired sample t-test analysis indicated a significance value of 0.000 < 0.05 and tcount 13.912 > ttable 2.048, which means there was a significant difference between the pre-test and post-test results. Therefore, it can be concluded that the use of the Wordwall educational game has a significant effect on improving students’ English vocabulary mastery.